Transcriptomic Analysis Reveals Competitive Growth Advantage of Non-pigmented Serratia marcescens Mutants - Xiang, Tingting; Zhou, Wei; Xu, Cailing; Xu, Jing; Liu, Rui; Wang, Nuo; Xu, Liang; Zhao, Yu; Luo, Minhui; Mo, Xiaoxin; Mao, Zeyang; Wan, Yongji (Frontiers in Microbiology, 2022)
Serratia marcescens is a common bacterium well-known for the red secondary metabolite prodigiosin. However, color mutants have long been described. Non-pigmented strains can be found to exist both naturally and under laboratory conditions. It is unclear why S. marcescens loses prodigiosin synthesis capacity in certain conditions. In the present study, we find that the spontaneous color mutants arise within a few generations (about 5 passages) and rapidly replace the wild-type parent cells (about 24 passages), which indicates a growth advantage of the former. Although the loss of prodigiosin synthesis genes (pigA-N) is frequently reported as the major reason for pigment deficiency, it is unexpectedly that the whole gene cluster is completely preserved in the different color morphotypes. Comparative transcriptomic analysis indicates a dramatic variation at the transcriptional level. Most of the pig genes are significantly down-regulated in the color morphotypes which directly lead to prodigiosin dyssynthesis. Besides, the transcriptional changes of several other genes have been noticed, of which transcriptional regulators, membrane proteins, and nearly all type VI secretion system components are generally down-regulated, while both amino acid metabolite and transport systems are activated. In addition, we delete the transcription regulator slyA to generate a non-pigmented mutant. The ΔslyA strain loses prodigiosin synthesis capacity, but has a higher cell density, and surprisingly enhances the virulence as an entomopathogen. These data indicate that S. marcescens shuts down several high-cost systems and activates the amino acid degradation and transport pathways at the transcriptional level to obtain extra resources, which provides new insights into the competitive growth advantage of bacterial spontaneous color mutants.